Search training for people with visual field loss after stroke: A cohort study. (May 2018) - Turton, Ailie J; Angilley, Jayne; Longley, Verity; Clatworthy, Philip; Gilchrist, Iain D
Introduction: People with visual field loss after stroke often experience difficulties in everyday activities. The purpose of this study was to assess the acceptability of search training as used within occupational therapy and the feasibility of possible measures for use in a future trial. Method: Nine participants took part in a goal oriented intervention that was delivered three times a week for 3 weeks. Patient reports of acceptability and outcomes using the Visual Function Questionnaire-25 were collected. Participants' room-search behaviour before and after the intervention was recorded using a head-worn camera. Results: Eight participants completed nine treatment visits. All participants reported improved awareness and attention to the blind side during activities following the intervention. Seven participants' change scores on the Visual Function Questionnaire-25 exceeded six points. Patterns of head-direction behaviour and overall room-search times were variable across patients; markedly, improved performance was only evident in the most severely affected participant. Conclusion: The intervention was acceptable. The Visual Function Questionnaire-25 is a feasible measure for assessing patient-reported outcomes. While the room search was informative about individuals' behaviour, more sophisticated methods of gaze tracking would allow search processes to be determined in real-world activities that are relevant to patients' goals.